Let’s play with colours: BacaMAX user interface for dyslexic children - Husni, Husniza; Jamaludin, Zulikha (Springer International Publishing, 2013)
Reading difficulties are synonymous with dyslexic children, whose unique condition is due to dyslexia.One of the major theories of dyslexia is visual deficits which are not caused by the problems with the eyes but with the information processing that took place inside the brain.Hence, to assist dyslexic children reading we propose BacaMAX, a visually stimulating voice replay application designed carefully to ease them reading.The application is a result of years of study on dyslexic children and their colour choices.Bedside experiment with the children was carried out on a systematic background and a foreground colour scheme, specifically on syllables, words, and short sentences.This paper aims to deliberately discuss BacaMAX interface design that started with our beta version to the current improved version.Rapid application development is employed as the methodology to develop prototypes and user acceptance test is employed to test the prototypes on real users. As the result, all versions are presented and discussed.